The use frequency of 10 different methods for preventing and detecting academic dishonesty and the factors influencing their use - Sattler, Sebastian (Studies in higher education, 2017)
This study examines the use frequency by German faculty of 10 different methods for preventing and detecting cheating on exams, plagiarism, and falsification and/or fabrication of data. It also investigates the factors influencing their use. In total, 3655 faculty members from 55 randomly chosen disciplines at 4 German universities were contacted and asked to participate in a web-based survey. Our results show that some methods were applied (very) seldom (e.g. the use of text-matching software), while others were used more frequently (e.g. employing a sufficient number of supervisors for exams). Factors found to promote the increased use of many of these methods include those methods' perceived efficacy as well as external expectations that they be used. When the effort involved in applying a specific method is perceived as high, the frequency of use is reduced. Our results can help universities to improve the prevention and detection of academic dishonesty.